2004
DOI: 10.1115/1.1772403
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of Hybrid Diffusers for Gas Turbine Combustors

Abstract: The increasing radial depth of modern combustors poses a particularly difficult aerodynamic challenge for the pre-diffuser. Conventional diffuser systems have a finite limit to the diffusion that can be achieved in a given length and it is, therefore, necessary for designers to consider more radical and unconventional diffuser configurations. This paper will report on one such unconventional diffuser; the hybrid diffuser which, under the action of bleed, has been shown to achieve high rates of diffusion in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…11 show that at 4% bleed the diffuser flow separates. This was surprising as the previous work of Walker et al [21,22] and some preliminary 2D axisymmetric predictions suggested that in this configuration the flow would remain attached. Flow separation occurs in line with the OGV wake as the low-momentum wake fluid is unable to overcome the increased adverse pressure gradient.…”
Section: Representative Inlet Conditions Were Taken From Experimentalmentioning
confidence: 68%
See 3 more Smart Citations
“…11 show that at 4% bleed the diffuser flow separates. This was surprising as the previous work of Walker et al [21,22] and some preliminary 2D axisymmetric predictions suggested that in this configuration the flow would remain attached. Flow separation occurs in line with the OGV wake as the low-momentum wake fluid is unable to overcome the increased adverse pressure gradient.…”
Section: Representative Inlet Conditions Were Taken From Experimentalmentioning
confidence: 68%
“…Consequently, a hybrid bled diffuser was designed based on the work of Walker et al [21,22]. This hybrid diffuser (Fig.…”
Section: Hybrid Pre-diffusermentioning
confidence: 99%
See 2 more Smart Citations
“…Britchford et al [20] demonstrated the superiority of the Reynolds stress model over a k-" model in capturing the combined effects of strong pressure gradients and streamline curvature in an annular S-shaped duct. Similarly, Walker [21] also showed that a Reynolds stress model gave better agreement with measured data in a dump diffuser combustion system.…”
Section: Numerical Methodologymentioning
confidence: 85%